Enhancing seed supply in mussel aquaculture: a cryopreservation study using two cooling systems - Meis-Solla, Adrian; Iglesias, Anxo; de Santiago-Meiide, Jose; Souza Troncoso, Jesús; Paredes Rosendo, Estefania (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):233